PENYULUHAN DIET DASH HIPERTENSI PADA LANSIA SELAMA MASA PANDEMI COVID-19 - Wisnu Widyantoro (UNIVERSITAS BHAMADA SLAWI, 2022)
The DASH (Dietary Approaches To Stop Hypertension) diet is one way to reduce hypertension. Dietary factors are important things to consider in patients with hypertension. Patients with hypertension should adhere to the DASH diet in order to prevent further complications. Therefore, counseling for the elderly is needed to understand the DASH diet. This activity aims to increase the knowledge and attitudes of the elderly about the hypertension DASH diet and how to process food for the hypertension DASH diet. The method used is counseling for the elderly who have hypertension who are selected by the Puskesmas staff as the person in charge of the posyandu for the elderly. The elderly understand the DASH diet for hypertension, which is characterized by being able to answer questions about how to process food. The elderly can also mention the type of food for the DASH hypertension diet and want to apply it in their daily diet. During the activity process, the participants/elderly listened, had discussions and were able to discuss or ask questions with the presenters.